Research on the design and policy of national number portability service plan - Wei DAI (Dianxin kexue)
The 2019 government work report proposed to make the service of number portability officially in effect nationwide.The preparation works had encountered many challenges, such as upgradation of network, changes of rules, and regulations.Firstly, an complete implementation plan from two aspects was proposed: service interaction and system support, including portability procedure, user interface, system structure and service enquiry.Secondly, operational regulations and policies related to number portability was analyzed and researched, and optimized suggestions were put forward.Finally, the present portability development status was summarized and the future development trend was predicted.China Telecom has maintained the leading position, the lowest complaints and system failures in the industry.Proposed policies regarding supervision have been adopted by the industry.